2017
DOI: 10.17219/dmp/70545
|View full text |Cite
|
Sign up to set email alerts
|

Bond strength of a resin composite to MTA at various time intervals and with different adhesive strategies

Abstract: Background. MTA cannot be used as a single restorative material due to poor esthetics and mechanical properties. Resin-based composite is often placed on top of MTA. Optimal time of doing that and the most effective bonding strategy have not been clearly determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…As far as the choice of the adhesive strategy is concerned, prior, welldocumented studies assessing the bond strength of a composite to MTA suggested the superiority of the TE technique over the SE systems. [15][16][17] However, reports on similar studies regarding Biodentine are ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…As far as the choice of the adhesive strategy is concerned, prior, welldocumented studies assessing the bond strength of a composite to MTA suggested the superiority of the TE technique over the SE systems. [15][16][17] However, reports on similar studies regarding Biodentine are ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that placement of composite used with a two-step etch and rinse adhesive (E&R) over white MTA performed significantly better than an all-in-one system in terms of bond strength [76]. Other studies concluded that the highest bond strength was obtained when the E&R adhesive was used after 24 h resulting in shear bond strength (SBS) of 7.3 ± 1.49 MPa [77,78]. Supplementary surface treatment protocols were investigated to reliably asses SBS after final composite restoration (Table 3).…”
Section: Mineral Trioxide Aggregatementioning
confidence: 99%
“…Concerning resin modified glass ionomer, Alqahtani et al (4) had mentioned that when Fuji II LC resin modified glass ionomer was immediately placed on ProRoot MTA it revealed statistically higher shear bond strength than the delayed placement. Several studies (4,(28)(29)(30)(31) had correlated the relatively strong bond of resin modified glass ionomer to the unset MTA based material could be related to the ability of formation of chemical bonding between the carboxylate anions (RCOO−) in the polyacrylic acid and the calcium in the MTA during its setting. On the contrary, those studies had declared that the premixed bio-ceramic (Neoputty) had responded in a contradictory way to either ProRoot MTA or NeoMTA2 concerning the immediately placed resin modified glass ionomer; as Neoputty had revealed lower shear bond strength values on being immediately restored compared to the delayed restoring.…”
Section: Discussionmentioning
confidence: 99%
“…This was attributed to the need of the premixed bio-ceramic Neoputty for moisture from external sources to start the setting reaction. (4,(28)(29)(30)(31) Thus, when dealing with premixed bio-ceramics it was found not preferable to immediately place the resin modified glass ionomer on top. Consequently, in accordance to the recommendations of the previously conducted researches, the present study went through the delayed restoration technique, and NuSmile-Neoputty specimens were left stored for 7 days before placement of the restorative materials.…”
Section: Discussionmentioning
confidence: 99%